Circulating and platelet-derived microparticles in human blood enhance thrombosis on atherosclerotic plaques - Suades, Rosa; Padró, Teresa; Vilahur, Gemma; Badimon, Lina (Thrombosis and Haemostasis, 2012)
Plaque rupture followed by thrombosis is the underlying cause of the majority of acute coronary syndromes. Circulating microparticles (cMPs), membrane blebs released into blood by activated cells, have been associated to vascular diseases. Specifically, high levels of platelet-derived microparticles (pMPs) have been found in patients with coronary disease. However, it is unknown whether microparticles have a contributing role to the development of damaged vessel wall-induced arterial thrombi. The aim of this proof of concept study was to investigate whether an increased number of cMPs and pMPs could functionally contribute to blood thrombogenicity on areas of arterial damage. Microparticles were isolated from blood of healthy volunteers and were characterised by flow cytometry. Effects of microparticles on platelet deposition were assessed under controlled flow conditions exposing damaged arterial wall in the Badimon perfusion chamber and collagen type-I in the flat perfusion chamber to human blood. Platelet deposition on damaged arteries was significantly increased in cMP- and pMP-enriched bloods (p<0.05). pMPs also induced increase in platelet (p<0.05) and fibrin (p<0.05) deposition on human atherosclerotic arteries and in platelet adhesion to purified collagen surfaces. pMP-enriched blood induced a dose-dependent shortening of epinephrine/collagen closure time evaluated by PFA-100 (p<0.001), increased lowdose ADP-induced platelet aggregation by LTA (p<0.05), and decreased clotting time by thromboelastography (p<0.01). In conclusion, an increased content of cMPs and pMPs, even in normal blood conditions, enhance platelet deposition and thrombus formation. This study shows for the first time that, beyond biomarkers of cell activation, blood microparticles have functional effects on cardiovascular atherothrombotic disease.
Keywords: Aggregation; atherothrombosis; coagulation; microparticles; platelets